CORRELATION BETWEEN INTENSITY OF SOSIAL MEDIA INSTRAGRAM WITH THE LEVEL OF SELF ESTEEM AMONG STUDENTS - Hidayah, Ridhoyanti; Aryandari, Kadek (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Factors that influence self-esteem among young people are social environments. The social environment renders the individuals doing the interaction and one type of interaction which does not need of face to face is through social media such as Instagram. Objective: This study aimed to obtain the correlations between the intensity of using social media Instagram with the level of self-esteem among eleventh-grade youth in a public senior high school in Malang. Method: This research used cross-sectional design. A sample of this research was eleventh-grade youth of senior high school with 86 active Instagram users. Data collecting in this study used the purposive sampling technique. A questionnaire used in this research intensively used Instagram and self-esteem questionnaires on social media. The data analysis used the Spearman test. Result: The result showed that the intensity of using social media Instagram with the level of self-esteem of eleventh-grade youth were mostly in low categories, while self-esteem level was mostly in the high category. The outcome indicated that the significant value = 0.310 (p<0.05) and the correlation coefficient = 0.111. Conclusion: There was no significant correlation between the intensity of using social media Instagram with the level of self-esteem of eleventh-grade youth. Further research is to analyse the social media used by youths other than Instagram and its correlation to self-concept, include self-esteem.